Guyanese Mass Games: spectacles that "moulded" the nation in a North Korean way. Issue 2 (3rd April 2019) - Kwon, Vicki Sung-yeon
ABSTRACT: This paper examines the Guyanese Mass Games, multi-media spectacles of visual and performing arts initiated by the leader of the Co-Operative Republic of Guyana and performed by Guyanese artists and youth aided by North Korean artists. North Korea and Guyana staged the games as the postcolonial and anti-imperialist expression of a newly established socialist regime in the global South in the context of the Cold War. Staged annually from 1980 to 1992 as part of the national day celebrations, they sparked debate, antagonism, and ethnic and political conflict in Guyana. The encounter of North Korean artists and Guyanese artists resulted in the new cultural tradition of the Guyanese Mass Games, which incorporated elements of Guyana's local culture into the form of the North Korean Mass Games. The paper expands the method of "inter-referencing" to incorporate a cross-continental dimension to analyze the cultural event of the Mass Games in North Korea and Guyana. The analysis in this paper is grounded in archival materials relating to the Guyanese Mass Games, such as sketch paintings, choreography books, photos, and newspaper articles, and examines how the representation of the people and land in the Mass Games captures the ambivalent character of decolonization and modernization projects in the socialist regime of Guyana.